68 General Pediatric Skills – Are we Doing Enough During Training to Prepare Pediatricians for Practice?. (19th August 2020) - Komsa, Kendra; Ngo, Quang; Eltorki, Mohamed
Abstract: Background: Exposure to and training in acute care during pediatrics residency training varies. Furthermore, there is evidence that pediatric and neonatal resuscitative skills, like cardiopulmonary resuscitation, and management of acute care patients is often lacking. 1, 2 Several studies have shown that only 2.5 of every 1000 pediatric emergency department patients require significant resuscitative efforts 3 . Thus training for such an event is extremely important because mastering the skills involved are less likely to come with experience. Currently, it is unknown how comfortable community pediatricians feel managing acute care situations, nor if their comfort level changes depending on where they are trained. Objectives: Our study aimed to determine if the training general pediatricians receive is sufficient to achieve a high comfort level in acute care that is sustained after 5 years in practice. This study explored pediatricians' comfort levels with pediatric and neonatal acute care, as set out by the objectives of training in pediatrics from the Royal College of Physicians and Surgeons of Canada. Design/Methods: An anonymous cross-sectional survey was piloted to a random sample of pediatricians in the province of Ontario, obtained through the College of Physicians and Surgeons of Ontario. Demographic data regarding practice type and duration was collected as well as training data about courses done in Pediatric Advanced Life Support (PALS) and Neonatal Resuscitation Program (NRP). Using a five-point Likert scale, pediatricians were asked to judge their comfort with different pediatric and neonatal acute care skills and clinical vignettes. Comfort level ranking ranged from 1 (very uncomfortable) to 5 (very comfortable). Skills included are listed in Figure 1. Baseline characteristics were described using frequency measures of proportions and medians and interquartile ranges when appropriate. For general pediatricians and specialists, we used the Mann-Whitney test to determine if there is a difference between the mean sum ranks of comfort level depending on whether the pediatrician was practicing for more or less than 5 years. Results: One thousand surveys were mailed, of which 248 were completed (response rate = 24%). Among respondents, 142 (54%) practiced general pediatrics and 68 (32%) were specialists. The majority of respondents practiced in a city, large city or metropolis (84%). In total, 169 (81%) of all survey respondents and 37 (74%) of general pediatricians have been in practice for five years or more. For all respondents, 150 (64%) felt comfortable or very comfortable with neonatal resuscitation team lead. There was no difference in comfort level with leading a neonatal resuscitation team based on years of practice (less than 5 years versus greater than and equal to 5 years) (p=0.69). This result did not change when considering the general pediatrician only (p=0.14). Of all respondents, 113 (48%) felt comfortable or very comfortable with pediatric resuscitation team lead. There was a significant difference in comfort level with leading a pediatric resuscitation team based on years of practice (less than 5 years versus greater than and equal to five years) (p=0.03) with more comfort being seen over time. When analyzing only for general pediatricians, that difference became insignificant (p=0.07). No difference was found in reported comfort in most skills and length of time in practice. However, comfort level is significantly positively correlated with the number of times a skill was performed. Interestingly, a significantly negative correlation was found between comfort level as pediatric resuscitation team lead and number of years in practice (p=0.03). Conclusion: The findings of this pilot survey suggest that ensuring competence in acute care in residency training is of utmost importance given that comfort with pediatric and neonatal resuscitation appears to remain static over time. The skills that pediatricians report most discomfort in are a target for continuing professional development or should be revised in the objectives of training of pediatrics.